THE USE OF AUGMENTED INTELLIGENCE AND ARTIFICIAL INTELLIGENCE IN SECOND LANGUAGE ENGLISH LEARNING IN HIGHER EDUCATION AT PUBLIC AND PRIVATE UNIVERSITIES IN PERU - RIVERA, JIMMY RONALD RIOJAS (2024)
WITH THE ADVANCEMENT OF TECHNOLOGY, NUMEROUS POSSIBILITIES ARE EMERGING. FOR EXAMPLE, THE FIELD OF LINGUISTICS IS CLEARLY AFFECTED BY THESE TECHNOLOGICAL IMPROVEMENTS. THEREFORE, THE STUDY AIMED TO ANALYZE THE USE OF AUGMENTED ARTIFICIAL INTELLIGENCE FOR SECOND LANGUAGE (L2) ENGLISH LEARNING. FOR THE STUDY, PRIMARY DATA WAS COLLECTED FROM A SAMPLE OF 135 STUDENTS, AND A SEQUENTIAL MIXED-METHODS ANALYSIS WAS CONDUCTED. THE RESULTS SHOWED THAT VOCABULARY CAN BE EXPANDED, PRONUNCIATION CAN BE IMPROVED, AND WRITING HAS ENHANCED DUE TO THE USE OF AI. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.